Literary Border Crossing and Cultural Belonging in Frederick Schiller Faust’s The Gentle Gunman - Lee, Susan Savage (American Studies in Scandinavia, 2023)
When Frederick Faust wrote The Gentle Gunman, locating it in Argentina, he did more than entertain American readers with new terrain in his western. By choosing to bordercross between the western and the Argentine gauchesque, he creates an opportunity to ask questions about the modernity of American and Argentine cultures and the national identities emphasized by both societies. This article begins by analyzing the characteristics of the western and the gauchesque in Faust’s novel. This article also provides an overview of the historical moment of the novel’s creation, expectations of readers from the time period, and Faust’s decision to eroticize the western’s setting. By doing so, this article answers the question about the hero’s displacement in a modern world that values class elitism above heroic characteristics. While scholars have analyzed different elements of Faust’s life and works, they have not discussed his border-crossing between the literary genres of the western and the gauchesque, two genres that emphasis national identity. By focusing on Faust’s border-crossing, it will become evident that Faust championed specific traits embodied by the cowboy and, in one case, the gaucho––all of which foster a sense of who belongs to the landscape and who does not.